Pyatiletniy plan, 1928 g. - Deni, Viktor; Dolgorukov, Nikolai (ОГИЗ - ИЗОГИЗ (Izogiz), 1967)
Top panel: red hand holding a booklet titled Five Year Plan with capitalist sneering. Bottom panel: Scenes of agriculture, industry, infrastructure, and flying red flags with capitalist weeping 1967 reproduction of 1933 poster art. Original title: Пятилетний план, 1928 г. PO-1047